2020
DOI: 10.1002/glia.23914
|View full text |Cite
|
Sign up to set email alerts
|

Sox2‐dependent maintenance of mouse oligodendroglioma involves the Sox2‐mediated downregulation of Cdkn2b, Ebf1, Zfp423, and Hey2

Abstract: Cancer stem cells (CSC) are essential for tumorigenesis. The transcription factor Sox2 is overexpressed in brain gliomas, and is essential to maintain CSC. In mouse high‐grade glioma pHGG cells in culture, Sox2 deletion causes cell proliferation arrest and inability to reform tumors after transplantation in vivo; in Sox2‐deleted cells, 134 genes are derepressed. To identify genes mediating Sox2 deletion effects, we overexpressed into pHGG cells nine among the most derepressed genes, and identified four genes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Thus, reducing astrogliosis through cell cycle inhibition improves axonal regeneration and functional recovery after TBI (Di Giovanni et al, 2005; Zhai et al, 2022). Of note, Sox2 controls the proliferation/self‐renewal of stem cells and glial cells under both normal physiological and pathological conditions through its target genes regulatory network (Barone et al, 2021; Mercurio, Serra, & Nicolis, 2019; Zhang, Zhu, et al, 2018). Consistent with the role of Sox2 in inhibiting the proliferation of reactive astrocytes and astrocytic‐scar formation after cortical injury in the adult mouse brain (Chen et al, 2019), our results demonstrated that Sox2 deficiency in astrocytes promotes neuronal regeneration and tissue recovery after cortical injury during the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, reducing astrogliosis through cell cycle inhibition improves axonal regeneration and functional recovery after TBI (Di Giovanni et al, 2005; Zhai et al, 2022). Of note, Sox2 controls the proliferation/self‐renewal of stem cells and glial cells under both normal physiological and pathological conditions through its target genes regulatory network (Barone et al, 2021; Mercurio, Serra, & Nicolis, 2019; Zhang, Zhu, et al, 2018). Consistent with the role of Sox2 in inhibiting the proliferation of reactive astrocytes and astrocytic‐scar formation after cortical injury in the adult mouse brain (Chen et al, 2019), our results demonstrated that Sox2 deficiency in astrocytes promotes neuronal regeneration and tissue recovery after cortical injury during the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing astrogliosis through cell cycle inhibition improves axonal regeneration and functional recovery after TBI (Di Giovanni et al, 2005;Zhai et al, 2022). Of note, Sox2 controls the proliferation/self-renewal of stem cells and glial cells under both normal physiological and pathological conditions through its target genes regulatory network (Barone et al, 2021;Zhang, Zhu, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among the CSC markers, the Sex-determining region Y (SRY)-box (SOX) factors are a family of transcriptional regulators that carry out crucial functions during embryonic development [ 9 , 10 , 11 ]. Previous experiments of our group in mouse high-grade gliomas identified a network of critical tumor-suppressive Sox2 targets, whose inhibition is involved in glioma CSC maintenance, therefore defining new therapeutic targets [ 12 ]. Herein, we evaluated the expression of SOX2 in a series of recurrent and progressive meningiomas in order to assess its prognostic role.…”
Section: Introductionmentioning
confidence: 99%
“…HEY2, one of the most prominent Notch pathway target genes, encodes a transcription factor [ 71 ]. Halani et al proposed that the loss of the Notch pathway activity and particularly of Hey2 levels were correlated with oligodendroglioma [ 72 ].…”
Section: Discussionmentioning
confidence: 99%